Prognostic Factors Associated with Clinical Improvement Following Energy-Based Device Treatment in Thai Patients with Atrophic Acne Scars: A Retrospective Study - Chadakan Yan; Phichayut Phinyo; Yuri Yogya; Mati Chuamanochan; Rungsima Wanitphakdeedecha (Dermatology and Therapy)
Abstract Introduction Acne scarring is a prevalent complication of acne vulgaris, often resulting in significant psychosocial distress. While energy-based devices (EBDs), including fractional laser (FL) and fractional radiofrequency (FRF), are increasingly used for atrophic acne scars, limited data exist on prognostic factors predicting treatment outcomes, particularly in Asian populations. The study aims to identify clinical predictors of graded clinical improvement in patients with atrophic acne scars treated with FL and FRF. Methods This retrospective cohort study was conducted at a university hospital in Bangkok, Thailand, from 2012 to 2023. Clinical improvement was assessed using standardized photographic evaluations and categorized into four levels: < 25%, 25–50%, 51–75%, and > 75% improvement. Univariable and multivariable ordinal logistic regression models were used to determine prognostic factors. Sensitivity analyses were performed to confirm the robustness of the findings. Results A total of 397 patients were included, of whom 254 received FL and 143 received FRF treatments. Older age (per 5-year increase) (mOR: 1.24; 95% CI: 1.07–1.43), male sex (mOR: 1.29; 95% CI: 1.06–1.57), shorter scar duration (per 5 years) (mOR: 0.73; 95% CI: 0.56–0.97), lower Fitzpatrick skin phototypes, and completion of at least three treatment sessions (mOR: 1.33; 95% CI: 1.16–1.53) were independently associated with greater clinical improvement. Sensitivity analyses confirmed the robustness of these associations. Conclusions Key clinical factors, including patient age, sex, scar duration, skin phototype, and completion of at least three treatment sessions, significantly influence treatment outcomes with EBDs. These findings support the development of personalized treatment strategies to optimize outcomes, particularly in patients with severe scarring. The trial registration number TCTR20240512006.